PENGARUH PEMBELAJARAN BERBASIS MASALAH (PBM) DENGAN PENDEKATAN OPEN-ENDED PROBLEM TERHADAP KEMAMPUAN BERPIKIR KRITIS MATEMATIKA SISWA SMP - Vebriana, Yemima Hendry; Ariyanti, Gregoria (Educatio Vitae, 2015)
This research aims to determine: whether there is a difference in students' critical thinking skills that are taught math using Problem Based Learning (PBM) with the Open-Ended Problem approach and the students’ critical thinking abilityof mathematics which are taught using conventional learning. This research is quantitative. The research was conducted in the second semester of academic year 2014/2015 in SMPN 6 Madiun with a population of class VII. While the sample is VIIH classes are taught using Problem Based Learning (PBM) with the approach of the Open-Ended Problems and VIIG classes are taught using conventional learning. Data collection techniques using the test method. The sampling technique in this study using cluster random sampling. The instruments used in the test method is a test of critical thinking skills. Critical thinking skills math test used to determine students' critical thinking skills in solving mathematical problems. The research instrument is a matter of critical thinking skills test is validated before tested. Based test for normality and homogeneity tests showed that samples of normal distribution and variants from the population with homogeneous, then the statistical test followed by t test. The result showed that there were differences in the ability of critical thinking math students taught using Problem Based Learning (PBM) with the approach of the Open-Ended Problem math and critical thinking skills of students who are taught using conventional learning. Keywords: Problem Based Learning (PBM) with the approach of the Open-Ended Problem math, conventional learning, critical thinking skills math.